2014
DOI: 10.1038/pr.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific relationship between prenatal exposure to phthalates and intrauterine growth restriction

Abstract: Background:No study has examined the association between prenatal phthalate exposure and intrauterine growth retardation (IUGR). This study aimed to investigate whether prenatal exposure to phthalates was associated with increased risk of IUGR. Methods: A total of 126 mother-newborn pairs, including 42 IUGR cases and 84 control newborns and their mothers, were enrolled in this case-control study. Spot urine samples were collected during the third trimester of pregnancy, and 5 phthalate metabolites (mono-n-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 39 publications
0
36
1
Order By: Relevance
“…39, 40 Additionally, the majority of these studies had sample sizes of ~200 or smaller. 14, 20, 41-43 These previous investigations have had mixed, but largely null, results. 10, 13, 14, 20, 23, 38, 41-46 The largest studies (n~300-400) reported null associations between phthalate metabolite measurements from spot urine samples collected during pregnancy and birthweight, length, and head circumference.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…39, 40 Additionally, the majority of these studies had sample sizes of ~200 or smaller. 14, 20, 41-43 These previous investigations have had mixed, but largely null, results. 10, 13, 14, 20, 23, 38, 41-46 The largest studies (n~300-400) reported null associations between phthalate metabolite measurements from spot urine samples collected during pregnancy and birthweight, length, and head circumference.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we examined adjusted models stratified by infant sex as previous studies have identified sex differences in these relationships (Models 3 and 4 for males and females, respectively). 14 Differences in coefficient estimates from male vs. female models were tested using a z statistic. We additionally created cross-sectional models with z-scored growth measures from visits 2-4 with the corresponding cumulative exposure metrics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study found associations between higher in utero exposure to certain phthalate metabolites and intrauterine growth restriction. 21 Interestingly, a greater proportion of Non-Hispanic black women have infants born small-for-gestational age compared to other racial/ethnic groups, 35 which is likely related to a host of factors, but could also be partly due to higher phthalate exposure in utero. Higher phthalate levels could explain some portion of racial/ethnic differences in maternal health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in pregnant women, higher urinary phthalate metabolite concentrations are associated with preterm birth 461920 and intrauterine growth restriction. 1921 In the offspring, in utero exposure to higher levels of phthalates is associated with changes in reproductive organ development, 5 eczema and allergic conditions, 22 as well as adverse neurobehavioral outcomes in children. 22325 While previous studies have evaluated the variability of phthalate levels across pregnancy, 2627 no study has characterized phthalate metabolite levels by race/ethnicity in a multi-racial population of pregnant women.…”
Section: Introductionmentioning
confidence: 99%